Examining the relationship between birth weight and attention-deficit hyperactivity disorder diagnosis - Ni, Meng; Li, Lijuan; Li, Wei; Zhang, Qianqian; Zhao, Jiuru; Shen, Qianwen; Yao, Dongting; Wang, Tao; Li, Baihe; Ding, Xiya; Qi, Sudong; Huang, Xiaoyi; et al. (Frontiers in Psychiatry, 2023)
Background: Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition that is prevalent in children worldwide. We evaluated the potential relationship between birth weight and ADHD using newly released data from the National Survey of Children’s Health 2019-2020. Methods: This population-based survey study used parent recollection data that were collected and submitted by 50 states and the District of Columbia to the National Survey of Children’s Health database from the National Survey of Children’s Health database. Those aged < 3 years and without birth weight or ADHD records were excluded. Children were stratified according to ADHD diagnosis and birth weight: very low birth weight (VLBW, < 1500 g), low birth weight (LBW, 1500–2500 g), and normal birth weight (NBW, ≥ 2500 g). Multivariable logistic regression was applied to examine the causal association between birth weight and ADHD while controlling for child and household characteristics. Results: The final sample consisted of 60,358 children, of whom 6,314 (9.0%) were reported to have an ADHD diagnosis. The prevalence of ADHD was 8.7% in NBW children, 11.5% in LBW, and 14.4% in VLBW. Compared with NBW children, LBW children (adjusted odds ratio [aOR], 1.32 [95% CI, 1.03–1.68]), and VLBW children (aOR, 1.51 [95% CI, 1.06–2.15]) had a significantly higher risk of ADHD after adjusting all variables. These associations persisted in the male subgroups. Conclusions and Relevance: This study found that LBW and VLBW children were at a higher risk of ADHD.